2023
DOI: 10.3389/fonc.2023.1162300
|View full text |Cite
|
Sign up to set email alerts
|

m6A modification on the fate of colorectal cancer: functions and mechanisms of cell proliferation and tumorigenesis

Abstract: N6-methyladenosine (m6A) is the most pervasive RNA modification in eukaryotic cells. The dynamic and reversible m6A modification of RNA plays a critical role in the occurrence and progression of tumors by regulating RNA metabolism, including translocation, mRNA stability or decay, pre-mRNA splicing, and lncRNA processing. Numerous studies have shown that m6A modification is involved in the development of various cancers. This review aims to summarize the significant role of m6A modification in the proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…The dynamic, reversible alteration of RNA m6A is essential for the development and spread of tumours. Oncogene and tumour suppressor gene m6A alteration research may provide fresh approaches to the detection and therapy of cancer 22 . The m6A alteration sites of NDE1 were examined via the SRAMP portal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic, reversible alteration of RNA m6A is essential for the development and spread of tumours. Oncogene and tumour suppressor gene m6A alteration research may provide fresh approaches to the detection and therapy of cancer 22 . The m6A alteration sites of NDE1 were examined via the SRAMP portal.…”
Section: Resultsmentioning
confidence: 99%
“…Oncogene and tumour suppressor gene m6A alteration research may provide fresh approaches to the detection and therapy of cancer. 22 The m6A alteration sites of NDE1 were examined via the SRAMP portal. There is a very strong probability that m6A may modify 15 of NDE1's functional regions.…”
Section: Resultsmentioning
confidence: 99%
“…These clues may be employed independently of other biomarkers to forecast the prognosis of CRC ( Lu et al, 2021 ). There is no denying that m 6 A modification is fundamental to CRC formation and advancement ( Jiang et al, 2023 ). On top of that, the mutual interaction mechanism between circRNAs and lncRNAs make them promising biomarkers in CRC.…”
Section: Biomarkers Of Ncrnas and M 6 A Regulators...mentioning
confidence: 99%
“…Therefore, the ability to identify prognostic risk factors of cancer types and understand their growth, progression, and treatments has been highly valued by researchers. Although genetic, genomic, and biochemical approaches have unveiled numerous molecular mechanisms that contribute to tumorigenesis, recent developments have shown that N 6 -methyladenosine (m 6 A) RNA modification is closely associated with both activation and inhibition of tumorigenesis ( Du et al, 2022 ; Ma et al, 2022 ; Zhang et al, 2022 ; Jiang et al, 2023 ). m 6 A RNA modification involves the attachment of a methyl group to the 6-carbon of adenosine, constituting a cotranscriptional and dynamically regulated mark catalyzed by a series of enzymes ( Leonetti et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%